Microstructures of Randall’s plaques and their interfaces with calcium oxalate monohydrate kidney stones reflect underlying mineral precipitation mechanisms - Sethmann, Ingo; Knoll, Thomas (Urolithiasis, 2017)
Randall’s plaques (RP) are preferred sites for the formation of calcium oxalate monohydrate (COM) kidney stones. However, although processes of interstitial calcium phosphate (CaP) plaque formation are not well understood, the potential of plaque microstructures as indicators of CaP precipitation conditions received only limited attention. We investigated RP-associated COM stones for structural details of the calcified tissues and microstructural features of plaque-stone interfaces as indicators of the initial processes of stone formation. Significantly increased CaP supersaturation can be expected for interstitial fluid, if reabsorbed ions from the tubular system continuously diffuse into the collagenous connective tissue. Densely packed, fine-grained CaP particles were found in dense textures of basement membranes while larger, laminated particles were scattered in coarse-meshed interstitial tissue, which we propose to be due to differential spatial confinements and restrictions of ion diffusion. Particle morphologies suggest an initial precipitation as metastable amorphous calcium phosphate (ACP). Morphologies and arrangements of first COM crystals at the RP-stone interface ranged from stacked euhedral platelets to skeletal morphologies and even porous, dendritic structures, indicating, in this order, increasing levels of COM supersaturation. Furthermore, these first COM crystals were often coated with CaP. On this basis, we propose that ions from CaP-supersaturated interstitial fluid may diffuse through porous RP into the urine, where a resulting local increase in COM supersaturation could trigger crystal nucleation and, hence, initiate stone formation. Ion-depleted fluid in persistent pores of initial COM layers may get replenished from interstitial fluid, leading to CaP precipitation in porous COM.